LEADERSHIP VILLAGE HEAD IN IMPLEMENTATION OF DEVELOPMENT IN VILLAGE KIE ICI DISTRICT DISTRICT OF WEST HALMAHERA DISTRICT. (STUDY IN KIE ICI VILLAGE - BALAIYE, FARNITA (JURNAL ADMINISTRASI PUBLIK, 2018)
This study aims to explain how the Leadership of Village Head In Implementation of Development in the Village kie Ici District District of Halmahera Barat. This research uses qualitative research methods, and data collection techniques used primary and secondary data obtained from village government and villagers with observation, interview and documentation, with the number of informants as many as 10 people. From the results of the survey conducted in the field of research can be seen the leadership of the village head for the field of physical development facilities are almost completely resolved while in the field of non-physical development has not been maximized and haru in increasing again the community also most strongly support any pembanguanna dilaksanaka in kie ici village. The results of this study are expected to contribute to the social sciences, especially the public administration discipline on the leadership of the village head in the implementation pembannguan in desakie ici can provide new thinkers for any forums that will be planned in the village, especially in kie ici village. Keywords: leadership, village head, development implementation.